What Should We Hope For? In Search of Reasonable Definitions of Success - Syse, Henrik (The review of faith & international affairs, 2024)
The criterion of “reasonable likelihood of success” clearly depends on a reasonable definition of success. This article suggests three such definitions and discusses these in light of the great uncertainty that accompanies any use of this forward-looking just war criterion. The importance of thorough understanding and knowledge, both military and cultural, in order for the application of the reasonable likelihood criterion to be meaningful is also discussed.